Research on Constant Torque Control of Electric Impact Wrench. Issue 1 (1st October 2022) - Wang, Xiaowu; Wu, Huanle; Tang, Nan; Fan, Xuewei; Qian, Long
Abstract : As a torque tool, the electric impact wrench is widely used in all kinds of works in life, and has a huge market demand in China. Aiming at the problem that the output cumulative torque of electric impact wrench cannot be accurately controlled, a control strategy based on motor speed and impact times is proposed in this paper. Firstly, inferring the proportion of each mechanism's energy to the total energy, and then the work on the nut can be calculated. Therefore, the trend of force on the nut can be predicted and calculated too. Finally, propose a scheme that the output torque of the electric impact wrench is controlled by the motor speed and the number of impacts within a certain error range.